Sonographically guided fine-needle aspiration biopsies of adrenal masses in lung cancer patients, eleven-year experience - Kocijančič, Igor (Radiology and oncology (Ljubljana), 2004)
Purpose. The aim of this retrospective study was to define the accuracy and safety of the ultrasonographically (US) guided fine-needle aspiration biopsy (FNAB) of the enlarged adrenals in the patients with lung cancer. Patients andmethods. In eleven-year period 64 patients with cytologically proven lung cancer underwent USguided FNABs of adrenal masses. The accuracy of the method was assessed on the basis of cytology findings and the safety on the number ofcomplications reported after the procedure. Results. US-guided aspiration biopsy turned out to be accurate in 58/64 cases (91%), and very safe with only4/64 (6%) minor complications. In 52/58 (90%) cases, the cytology sample was found to be malignant. In 6 cases (10%), isolated adrenal masses were adenomas. Conclnsions. We recommend US guided FNAB as a safe and reliable diagnostic method that has many advantages over computer tomography (CT) guided FNAB, such as safety, patient friendliness, no X-rays and its reproducibility.
Keywords: Adrenal Gland Neoplasms; biopsija; Biopsija igelna; Biopsy, Needle; diagnostika; Lung Neoplasms; Nadledvična žleza, novotvorbe; Neoplasm Metastasis; Novotvorba, metastaza; novotvorbe; onkologija; Pathology; pljučne bolezni; Pljučne novotvorbe; Secondary; tumor; Ultrasonography; ultrasound; ultrazvok